Aspetti metodologici ed evidenze empiriche della valutazione d’impatto di “Industria 4.0” nel settore manifatturiero italiano - Capuano, Giuseppe; Capuano, Martina (Argomenti, 2020)
The objective of the article is to estimate the stimulation of output on industries at a national level after the “Industry 4.0” plan. The article proposes an application of the Leontief model to assess the impact of “Industry 4.0” on Italian manufacturing industries thanks to output multipliers and to estimate the potential economic impact that the “Impresa 4.0” plan could have on the manufacturing production sectors within the next decade. The additional effect on the manufacturing potential output will be +0.13% per year for 10 years. JEL Classification: E02; L52; L60; O25